2021
DOI: 10.1007/s10815-021-02114-3
|View full text |Cite
|
Sign up to set email alerts
|

Live birth in a complete zona-free patient: a case report

Abstract: Objective To report a live birth from a patient with complete zona-free oocytes due to abnormal zona production and to reveal full time-lapse blastocyst development footage of its originating embryo. Methods A 34-year-old woman presented with a history of failed fertilization via standard in vitro fertilization insemination and a potential absence of zona pellucida. A total of 3 intracytoplasmic sperm injection cycles were undertaken with all oocytes collected being zona-free. Embryos created in the initial 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Moreover, it provides mechanical support by preventing blastomere separation during embryo development [37] . Several studies has reported the successful fertilization, embryo development, implantation, and live birth using ZP-free oocytes in IVF [36,[38][39][40][41][42][43] . However, there are several safety concerns about ZP-free oocytes such as mechanical damage during ICSI, loss of blastomeres during embryo culture until compaction, risk of mechanical damage during routine handling or embryo transfer, and comparatively less tolerant to vitrification.…”
Section: Ivf Laboratory Procedures And/or Interventions That Unintent...mentioning
confidence: 99%
“…Moreover, it provides mechanical support by preventing blastomere separation during embryo development [37] . Several studies has reported the successful fertilization, embryo development, implantation, and live birth using ZP-free oocytes in IVF [36,[38][39][40][41][42][43] . However, there are several safety concerns about ZP-free oocytes such as mechanical damage during ICSI, loss of blastomeres during embryo culture until compaction, risk of mechanical damage during routine handling or embryo transfer, and comparatively less tolerant to vitrification.…”
Section: Ivf Laboratory Procedures And/or Interventions That Unintent...mentioning
confidence: 99%
“…Following controlled ovarian stimulation and transvaginal oocyte aspiration as described previously [20], cumulus-oocyte-complexes were identified and cultured in GIVF + (Vitrolife, Gothenburg, Sweden) at 37 °C in 6% CO 2 , 5% O 2 , and 89% N 2 in a MINC incubator (Cook Medical, Eight Mile Plains, Queensland, Australia). At 39-h posttrigger injection, cumulus cells were removed using a diluted hyalase solution of 25 IU/ml (Hyalase®; Sanofi Aventis, Sydney, Australia) and mechanical action.…”
Section: Gamete Preparationmentioning
confidence: 99%